Caravaggio - Giorgi, Rosa.; Kruger, Anna. (New York : DK Pub., 1999)
Surveys the life and work of sixteenth-century Italian artist Caravaggio, analyzes his masterpieces, explains them in their historical and social context, and includes more than 300 full-color reproductions of his paintings.
Includes index.
Book Report.
Kliatt.
Wilson's Senior High School.
Young Adult
Keywords: Caravaggio, Michelangelo Merisi da, -- 1573-1610.; Caravaggio, Michelangelo Merisi da, -- 1573-1610.; Painting, Italian; Italian painting